Immersive AR pet game with hand motion - Chong, Jing Voon (2023)
This project aims to provide an engaging and interactive solution for individuals who desire the experience of owning a pet but cannot do so due to various constraints. The project will leverage Augmented Reality (AR) technology to create a virtual pet-raising game that offers a realistic and immersive experience. The game will incorporate hand-detection technology to enable intuitive interactions with virtual pets. ARCore, Unity and ManoMotion will be the primary game development tools. ARCore is compatible with most mobile devices. It uses the device's camera and internal sensor to detect the position and orientation of the environment, estimates light conditions and compute location changes. With these capabilities, ARCore can seamlessly blend virtual objects with the real world. Unity provides a cross-platform development environment for AR applications that run on different devices with varying capabilities. ManoMotion is a hand-tracking software that uses machine learning algorithms to track and recognise hand movements in real-time. It captures the hand movements using a camera and analyses the data to identify various gestures made by the user's hand. The software provides position coordinates and rotation values in three-dimensional space and distinguishes between left and right hands. ManoMotion provides gesture analysis to interpret users' intentions, allowing developers to create customised experiences catering to different behaviours.